A Novel Technique for the Damage Control of Huge Diaphragmatic Injuries - Kessel, Boris; Reva, Victor; Sheffer, Daniel; Hörer, Tal (Journal of Endovascular Resuscitation and Trauma Management, 2020)
Background: Diaphragmatic injuries are rare in trauma victims, and mostly located on the left side. The standard approach is primary closure, using non-absorbable heavy interrupted sutures. Right-sided injuries are protected by the liver and such repair is not mandatory. However, closure of large defects, not suitable for primary suture, remains a challenging problem, especially in a military setting or in severely multiple-organ injured patients. Up until now, the single surgical solution in such situations is usage of absorbable mesh. Methods: The feasibility of a damage control closure technique for huge traumatic diaphragmatic injury was evaluated. Results: After creation of large diaphragmatic defects in an animal model, the defects were closed with an appropriately sized plastic (Bogota) bag and using a large abdominal pad, accordingly. The total procedure time was about 3 min and no chest re-protrusion was observed until completion of the experiment. Conclusions: This novel method is likely to be safe and simple to use as a damage control method and should be further investigated in proper models and clinically.